2022
DOI: 10.1007/s10639-021-10843-2
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and interaction practices towards distance education during the pandemic

Abstract: The COVID-19 pandemic has affected educational institutions deeply and globally. In the course of the pandemic, countries around the world have tried to fill the gap that has arisen in traditional face-to-face education with emergency web-based distance education systems. This study aims to evaluate the possibilities and limitations of emergency distance education conducted during the pandemic period, based on university students' approach-avoidance attitudes towards distance education and their distance educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…These questions urgently require further empirical research to guide vocational education teachers in designing online interactions that are adaptable to different contexts. This conclusion is similar to that of Yazgan (2022) regarding the weakened interaction in ERT and the emergence of new effects.…”
Section: Learning: Insufficient Practical Training Coverage and Studentsupporting
confidence: 86%
See 1 more Smart Citation
“…These questions urgently require further empirical research to guide vocational education teachers in designing online interactions that are adaptable to different contexts. This conclusion is similar to that of Yazgan (2022) regarding the weakened interaction in ERT and the emergence of new effects.…”
Section: Learning: Insufficient Practical Training Coverage and Studentsupporting
confidence: 86%
“…For example, the satisfaction levels of students from institutions Y, W, X, S, H, and N were 80.0%, 87.4%, 86.0%, 73.9%, 70.0%, and 23.6%, respectively. This conclusion is consistent with that of Yazgan (2022). In this regard, to better promote and implement blended learning or online teaching on a larger scale in vocational colleges, it is important to explore the reasons behind the low levels of student satisfaction and acceptance.…”
Section: The Problems With Implementation Of Ert Activitiessupporting
confidence: 85%
“…To assess the pedagogical relevance of distance education, in-depth scientific studies and expert opinions were mobilized. Various instruments and constructions have been suggested [7]- [16]. Although each of the instruments remains relevant and aims to address the different dimensions of distance education, but they are too focused on the learner and the infrastructure; the teaching is a bit neglected in the process of distance learning assessment.…”
Section: Evaluation Of the Pedagogical Relevance Of Distance Educationmentioning
confidence: 99%
“…Most teachers believed that students' psychology was negatively affected during the COVID-19 pandemic process, but there were also students who could adapt to this process. Yazgan (2022) recently investigated the possibilities and limitations of emergency distance education conducted during the pandemic period based on university students' attitudes toward distance education and their experiences. The results showed that during distance learning, students' avoidance attitude toward distance learning was more robust than their approach attitude.…”
Section: Education and Training Practices In Tr During The Pandemic P...mentioning
confidence: 99%